Metal‐ and Photoredox‐Catalyst Free Unified Approach for the Synthesis of Azole‐Fused Quinolines via tert‐Butyl Nitrite‐Mediated Regioselective Annulation. Issue 4 (26th February 2022) - Barak, Dinesh S.; Dahatonde, Dipak J.; Batra, Sanjay
Abstract: A metal‐ and photoredox‐catalyst free unified approach for the synthesis of azole‐fused quinolines via annulation reaction between substituted 5/2‐amino‐ N ‐phenyl azoles and alkynes in the presence of tert ‐butyl nitrite ( t ‐BuONO) in acetonitrile is reported. The reaction that proceeds via radical mechanism afforded solid products, which separated out in the reaction mixture and were isolated by filtration only. The participation of the azole substrate in the reaction ensued only if a functional group capable of accepting hydrogen was present on carbon adjacent to the carbon bearing the amino group. It is anticipated that such functional group facilitated stabilization of the diazoether transition state via hydrogen bonding. Abstract : tert ‐Butyl nitrite‐mediated regioselective annulation reaction is presented between substituted 5/2‐amino‐ N ‐phenyl azoles and alkynes in acetonitrile for the synthesis of azole‐fused quinolines.